Comparative Analysis of Bank Health Levels Using the RGEC Method at PT. Bank Mandiri Tbk and PT Bank Central Asia Tbk Year 2018 - 2020 - Koeshardjono, R. Hery; Perwitasari, Dyah Ayu; Zahratul Qolbi, Novita Dewi (Ecobuss, 2024)
This research aims to determine the level of bank health at PT Bank Mandiri (Persero) Tbk compared to PT Bank Central Asia Tbk using the RGEC (Risk profile, Good Corporate Governance, Earnings, Capital) method for 2018-2020. This type of research uses quantitative descriptive research. The variables used by researchers are RGEC and Bank Health. The research subject is PT. Bank Mandiri (Persero) Tbk and PT. Bank Central Asia Tbk is listed on the Indonesia Stock Exchange (BEI) for 2018-2020. The object of this research is the annual report of the two banks. The data analysis method uses financial report analysis and GCG self-assessment reports for the RGEC method. The research results show that the average composite value for Bank Mandiri is 91% while BCA is 96.67%, meaning that in the RGEC analysis for assessment based on ratios (NPL, LDR, Self Assessment GCG, ROA, NIM, CAR) BCA bank has a higher level of health compared to Mandiri banks. Keywords: Bank Health, Composite Value, RGEC